A new system for stop motion camera movements. Issue 1 (1st December 2012) - Saini, Laura; Albrecht, Gudrun; Lissarrague, Nicolas; Romani, Lucia
This article presents a new system that allows the creation of realistic camera movements for a stop motion animation. The system improves traditional 3D software animation programs (e.g. Maya and 3D Studio Max) for creating stop motion camera movements by using a haptic interface. We describe the whole system and explain in detail the mathematical processing to obtain different camera movements by using a haptic interface for motion capture. The recorded haptic positions, once elaborated, are exported, frame by frame, to the motion control software, which calibrates the motion control robot, controls the camera settings and, finally, executes the sequences. A class of students of the 'Art plastiques et Création numérique' Master of the University of Valenciennes evaluated the system.